[Crowded Yosemite Hall common area] (1977)
Sixteen students sit, stand, or play table tennis inside the Yosemite Hall common room at Cal Poly, San Luis Obispo, on the South Mountain/Grand side. The floor is made of reflective and buried concrete and aggregate. Multiple chairs and couches of late 1970s period design sit throughout the space with students relaxing and studying in different parts of the space. One group sits in the foreground around a coffee table, some with their feet up, with decorations and an ashtray, while two play table tennis or ping pong and others look on. The very large windows, square lights in the recessed ceiling, and other architectural features are prominent.